Técnica, ética e natureza : desafios da moralidade ambiental na modernidade técnica. - Santana, Ivo Delmondes Freitas de (2011)
Technique offers new possibilities in every moment, constantly redefining the barrier of what is possible and impossible and therefore the scope of our action before the world and its beings. This increase in our power demands that ethics should be thought beyond man and predictability. The conscience of the contingency reminds us of the unstable character of modernity. We do not live in the world where the technique is inspired by the natural regularities and ethics in their cosmology. Nor do we live fully in the modern break that is radically opposed to nature. We are at the place where nature and culture get togheter so essentially that both change the limits of morality, technology and politics. In this research we propose to highlight the tension between Technique, Ethics and Nature in order to understand the new challenges of the modern environmental morality.